Influence of alkali treatment on physico-chemical properties of Malaysian bamboo fiber: A preliminary study = Pengaruh rawatan alkali terhadap sifat-sifat fizikal-kimia serat buluh Malaysia: satu kajian awal - Foo, Sheng Tong; Siew, Choo Chin; Mohd Tamizi, Mustafa; Huei, Ruey Ong; Khan, Maksudur R.; Jolius, Gimbun; Doh, Shu Ing (Universiti Kebangsaan Malaysia, 2018)
In the present study, the effect of alkaline treatment on the morphology and physico-chemical properties of Malaysian bamboo fibers was elucidated. The fibers were extracted from raw bamboo culm using alkaline solution with concentrations of 0 and 10 wt% at 24 hours and followed by roller milling techniques. The treated and untreated fibers were characterized by Fourier transform infrared spectroscopy (FTIR), thermogravimetric analysis (TGA) and scanning electron microscope (SEM). Apart from that, the mechanical properties of single fiber were also investigated. It was found that the tensile strength and modulus of the alkali-treated fiber were improved by 45.6 and 72%, respectively, compared to the untreated fiber. The surface morphology of the treated fiber was improved in which the surface roughness has been reduced significantly as proven in SEM. The FTIR and TGA data suggested that alkaline treatment gradually removed the lignin and hemicellulose. These findings highly recommended that, local bamboo fiber could be used as a reinforcement agent for composite making.